Roles of terpenoid Astragaloside IV in altered states of the nervous system: an updated review (Research, Society and Development, 2022)
Compounds of natural origin have been used by the human species in the treatment of various diseases since the most remote times, with many active principles being isolated in recent years. One of these compounds, Astragaloside IV (AS-IV), obtained from the root extract of Astragalus membranaceus, a plant native to southwestern Asia, has been particularly studied, possessing anti-inflammatory, antioxidant, antibacterial and antiviral properties. In this sense, the aforementioned substance has become a component used in several models of Central Nervous System (CNS) diseases. In light of this, the present review aimed to describe the roles of this substance in models of altered states of the CNS, focusing on Alzheimer’s and Parkinson’s Diseases, stroke and traumatic brain injury, debilitating conditions that result in a severe impact on both socioeconomic and health care systems. The antioxidant, anti-inflammatory and anti-apoptotic actions of AS-IV were characterized in both in vitro and in vivo models in the distinct pathologies investigated, indicating that this substance emerges as an important element for the treatment of altered states of the CNS.